Computing Education in the Era of Generative AI. - Denny, Paul; Prather, James; Becker, Brett A.; Finnie-Ansley, James; Hellas, Arto; Leinonen, Juho; Luxton-Reilly, Andrew; Reeves, Brent N.; Santos, Eddie Antonio; Sarsa, Sami (Communications of the ACM, 2024)
Challenges and opportunities faced by computing educators and students adapting to LLMs capable of generating accurate source code from natural-language problem descriptions.